(untitled) (Public Sector Economics - submission site, 2020)
Inheritance fundamentally violates the meritocratic justice principle of society. Despite the high level of wealth concentration and the fact that few people would be affected, political support for an inheritance tax is rather low. The topic of inheritance is not only about wealth but about values. We combine both by using questions in the Austrian Household Finance and Consumption Survey tailored to examine family values. The main aim of the paper is to bring sociological concepts and perceptions into the economic analysis of the role of inheritance in wealth distribution. We find several inconsistencies in people’s perceptions concerning the relation of inheritance to issues of social justice. We argue that family values are decisive for negative perceptions of inheritance taxation. Our empirical evidence suggests that in order to understand the resistance to inheritance taxation in society better, family values have to be taken into account.